1987
DOI: 10.1007/bf01297051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of desipramine on irritable bowel syndrome compared with atropine and placebo

Abstract: Antidepressant treatment trials of irritable bowel syndrome (IBS) have suggested beneficial effects. Twenty-eight patients with the disorder (9 constipation-predominant, 19 diarrhea-predominant) completed a double-blind crossover study using desipramine, atropine, and placebo in random sequence. A four-week observation period preceded three six-week test periods. Bowel habits, abdominal distress, and affect were reported daily and in biweekly evaluations. Psychological assessments and rectosigmoid contractile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(85 citation statements)
references
References 36 publications
2
83
0
Order By: Relevance
“…Their mechanism in IBS is not completely understood, but has been postulated to relate to an ability to modulate central and peripheral pain perception [110,111] , improve underlying psychiatric conditions, and possibly improve gut motility through modification of neurotransmitter activity [112,113] . Unfortunately, randomized-controlled trials to date have largely been hindered by poor study design and methodological flaws, making it difficult to judge the therapeutic value of these agents [114][115][116] . Most studies provide little evidence that antidepressants are superior to placebo in improving specific IBS-related symptoms, but some do suggest that overall global well-being may be improved.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Their mechanism in IBS is not completely understood, but has been postulated to relate to an ability to modulate central and peripheral pain perception [110,111] , improve underlying psychiatric conditions, and possibly improve gut motility through modification of neurotransmitter activity [112,113] . Unfortunately, randomized-controlled trials to date have largely been hindered by poor study design and methodological flaws, making it difficult to judge the therapeutic value of these agents [114][115][116] . Most studies provide little evidence that antidepressants are superior to placebo in improving specific IBS-related symptoms, but some do suggest that overall global well-being may be improved.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Moreover, trials should include baseline assessment of symptoms, account for patient disposition (discontinuations, withdrawals, etc), provide sample size calculation and enroll an adequate number of patients, with the primary outcome being improvement of global IBS symptoms based on patient assessment and/or use of a validated scale to assess IBS symptoms [3] . To date, 10 randomized, controlled trials and two crossover studies have evaluated the effectiveness of TCAs in the treatment of IBS [10][11][12][13][14][15][16][17][18] . The largest and best study to date on TCAs was done by Drossman et al [19] , investigating the role of desipramine in patients with functional disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis of randomized controlled trials concluded that the tricyclic antidepressants were superior to placebo in IBS with an number needed to treat (NNT) of 3 [51], although the individual trial results and the quality of the trials has been variable [52][53][54][55][56]. Greenbaum et al for example in a study of desipramine 150 mg daily separated diarrhoea from constipation-predominant IBS, and reported that diarrhoea, abdominal pain and depression but not constipation improved with active drug therapy, compared with atropine or placebo [52]. Ritchie & Truelove also reported that abdominal pain and diarrhoea but not constipation or bloating improved with a combination of nortryptiline 30 mg and fluphenazine 1.5 mg [53].…”
Section: Antidepressants and Anxiolyticsmentioning
confidence: 99%